Nanoindentation study on Gd-deposited YBaCuO superconductor - YILMAZ, F; UZUN, O; KOLEMEN, U; KILICASLAN, M F; BASMAN, N; ERGEN, S; OZTURK, K; YANMAZ, E (Springer Science and Business Media LLC, 2013)
Nanoindentation technique was used to characterize the mechanical properties of Gd-deposited bulk YBaCuO superconductors fabricated by solid-state reaction method. In order to determine the hardness and reduced modulus of the samples, load-displacement data were analysed by using the Oliver–Pharr method. The hardness values exhibited significant peak load-dependence especially at lower peak loads, while the reduced modulus values were found to be nearly constant at studied loading range. In order to find true hardness of the samples, the peak load-dependency of hardness was analysed by using Meyer’s law, minimum resistance model, elastic/plastic deformation model, energy balance model, Nix–Gao model and Mukhopadhyay approach. Of the aforementioned models, energy balance model and Mukhopadhyay approach were found to be the most effective models to explain the load-dependency of hardness.
Keywords: nano-indentation; indentation size effect; YBaCuO superconductor; Gd-deposition